2018
DOI: 10.1038/s41598-018-20927-8
|View full text |Cite
|
Sign up to set email alerts
|

An allogeneic ‘off the shelf’ therapeutic strategy for peripheral nerve tissue engineering using clinical grade human neural stem cells

Abstract: Artificial tissues constructed from therapeutic cells offer a promising approach for improving the treatment of severe peripheral nerve injuries. In this study the effectiveness of using CTX0E03, a conditionally immortalised human neural stem cell line, as a source of allogeneic cells for constructing living artificial nerve repair tissue was tested. CTX0E03 cells were differentiated then combined with collagen to form engineered neural tissue (EngNT-CTX), stable aligned sheets of cellular hydrogel. EngNT-CTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…Engineered neural tissue (EngNT) refers to anisotropic cellular hydrogels that have been developed for use in nerve repair to deliver Schwann cells or Schwann cell‐like therapeutic cells to mimic an autograft (Georgiou et al, ; Martens et al, ; Georgiou et al, ; Sanen et al, ; O'Rourke et al, ). This approach, however, also has the potential to be used as a model for pre‐clinical in vitro drug screening as it enables quantification of the regeneration of neurons within an aligned 3D Schwann cell‐seeded collagen gel environment.…”
mentioning
confidence: 99%
“…Engineered neural tissue (EngNT) refers to anisotropic cellular hydrogels that have been developed for use in nerve repair to deliver Schwann cells or Schwann cell‐like therapeutic cells to mimic an autograft (Georgiou et al, ; Martens et al, ; Georgiou et al, ; Sanen et al, ; O'Rourke et al, ). This approach, however, also has the potential to be used as a model for pre‐clinical in vitro drug screening as it enables quantification of the regeneration of neurons within an aligned 3D Schwann cell‐seeded collagen gel environment.…”
mentioning
confidence: 99%
“…A number of therapeutics for the treatment of PNI have been developed in animal models, including engineered tissues that mimic the regenerative microenvironment found in the nerve autograft and distal nerve segment [73,[79][80][81][82]. However, there are many challenges associated with the clinical translation of these and other therapies with the potential to improve nerve repair outcomes in patients.…”
Section: Challenge Of Clinical Translationmentioning
confidence: 99%
“…But after fresh nerve allograft transplantation by Davis et al [18], it was found that the area where it was operated on transplantation could not be fully restored. Considering that the transplanted nerves ended with central necrosis and fibrous scarring, Sunderland believed that using fresh nerve allograft was a failure [19]. At present, it is generally accepted in academia that rejection reaction between graft and recipient is the main factor affecting functional repair.…”
Section: Nerve Allograftmentioning
confidence: 99%